Downstreaming of bioactive peptides using nanocrystalline molecular sieves - Sharma, Manish Kumar (My University, 2014)
The potential applications of bacteriocins as food preservatives and their ability to inhibit the growth of pathogens has drawn the attention of researchers around the world. Due to its importance in various industrial applications, an innovative approach for their purification is required. In the present study, ability of zeolite for bacteriocin recovery is exploited. For this, two types of zeolites i.e., zeolite A and Na-X were synthesized from coal fly ash as cheap raw material. Cr ystallanity and microporous structure of zeolite was confirmed by SEM & XRD analysis. These zeolites were used to study the recovery of bacteriocin from lactic acid bacteria, LAB 4 and L. acidophilus ATCC 43121. Zeolite Na-X showed maximum recovery efficiency of 98% for LAB 4 and 97 % for ATCC 43121 with in a time span of 60 and 90 minutes respectively while with zeolite A maximum recovery efficiency of 95% with LAB 4 and 91% for L. acidophilus was observed at 60 and 90 minutes respectively. The results considered the application of zeolite in bacteriocin recovery & purification irrespective of bacteriocin concentration
MS, DBTS
Keywords: Bioactive peptides; Bacteriocin; Zeolites; Lactic acid bacteria